Evaluation And Association Of Periodontal Status With Level Of P. Intermedia In Chronic Periodontitis Female Patients With And Without Oral Contraceptive Pills Following Non-Surgical Periodontal Therapy Using Quantitative Polymerase Chain Reaction: An Int (Journal of Pharmaceutical Negative Results, 2023)
Aim : The aim of the present study was to detect and correlate the levels of Prevotella Intermedia with clinical parameters after nonsurgical periodontal therapy (NSPT) in chronic periodontitis female patients with or without oral contraceptive pills, using quantitative polymerase chain reaction (Q‑PCR) method.Materials and Methods : Sixty female patients equally divided into three groups,i.e. Periodontally health female patients (Group –I), females with Chronic Periodontitis (CP) without taking oral contraceptive pills(OCP) (Group-II), females with Chronic Periodontitis (CP) taking oral contraceptive pills(OCP) (Group-III) and were correlated for the presence of P. Intermedia in the respective groups. PPD, CAL, and saliva samples for microbiological evaluation were assessed at baseline, 1‑, and 3‑month post‑NSPT.Results : Significant reduction of PPD was found 2.4 ± 0.48mm versus 1.4 ± 0.37 mm in Group I, 4.8 ± 0.74 versus 2.8 ± 0.53 mm in Group II, and 6.6 ± 0.48 mm versus 4.4 ± 0.39 mm in Group III post‑NSPT at 3 months. Similarly, a notable reduction of CAL was exhibited in both Group II (5.4 ± 0.65 vs. 3.1 ± 0.42 mm) and Group III (6.6 ± 0.48 vs 3.6 ± 0.35 mm) patients after NSPT at 3 months. A greater reduction of P. Intermedia concentrations was observed in both Group II and Group III at 3‑month post‑NSPT.Conclusion : The substantial improvement of clinical parameters was found to be in correlation with the load of P. Intermedia, which was reduced more in Group II than in Group III, emphasizing the applicability and sensitivity of Q‑PCR method for its assessment.